Situation Report: Hungary, 13 January 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Decree on Social Origin Provokes Heated Dispute Decree Freezes Number of Administrative Workers Hungarian-Language Book Publishing in Romania Significant Rise in Exports of Meat to Western Countries Prospects for Tourism in 1976 Output of Small Farms Increasing in Importance